ANALYZING THE IMPACT OF CELEBGRAM ENDORSEMENT ON CUSTOMER PURCHASE INTENTION OF WOMAN CLOTHING OF INSTAGRAM USERS - Pangkey, Sesilia; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2020)
Abstract: Celebgram endorsement is a person who might influence Instagram users when they doing an endorsement.Â Customer purchase intention is a process when the Instagram users having the interest to purchase a product when seeing celebgram endorsement. The aim of this study is to analyze how is the impact of celebgram endorsement on customer purchase intention of womenâ€™s clothing. To achieve these objectives the researcher got information from 15 informants using a qualitative study which is an in-depth interview and uses purposive sampling. In order to get the best result, the researcher took the entire informants that have been ever bought clothes through celebrity endorsement. The results showed that Celebgram endorsement gives a significant impact on customer purchase intention, celebgram endorsement is one of the biggest factors that increase customer purchase intention, the credibility of celebgram endorsement can influence the customer to purchase the woman clothes on Instagram. They said that seeing the celebgram endorsement it stimulates them to purchase the products. Celebgram endorsement has an important role in influencing customer purchase intention with their credibility.Keywords: Celebgram Endorsement, Customer Purchase IntentionÂ